COMPARATIVE ANALYSIS OF THE PHYSICOCHEMICAL PROPERTIES OF AMINO ACID RESIDUES WITHIN THE VARIOUS EMBODIMENTS OF THE ENVELOPE PROTEIN E TICK-BORNE ENCEPHALITIS VIRUS - Yu. S. Bukin; Yu. P. Dzhioev; I. V. Kozlova; D. .. Ruzek; V. I. Zlobin (Acta Biomedica Scientifica)
The article considers variability of antigen protein E of different tick-borne encephalitis (TBE) strains at the level of physicochemical properties of amino acid residues. The authors evaluated variety of properties of protein amino acids involved in antigen-antibody interaction. 180 variants of TBEVE protein in database NCB1 were detected, differing in physical and chemical properties of amino acid residues. This implies that natural variants of TBEV strains can potentially be detected, that escaped from the immune response induced by standard vaccine.